MASLAHAH DALAM EKONOMI ISLAM KONTEMPORER STUDI FILSAFAT EKONOMI ISLAM - Harianto, Budi; Dharma, Budi (Islamijah: Journal of Islamic Social Sciences, 2022)
This article describes people's lives in the economy which are usually carried out individually or even in groups, either in a family, organization, or even a group of people who usually try to find a way to find the best way to fulfill their own economy. In Islam itself, at the beginning of the discussion, Islam often seemed classic, only focused on the metaphysical-transidental-normative area, without facing a future that is now a lot. Philosophy as the deepest aspect that influences human behavior is seen as something essential in providing solutions that occur in contemporary society, including one of contemporary Islamic economics. This research is a library research. Extracting information using the documentary method, reviewing and reviewing documents from various related sources. The results of the study indicate that in contemporary Islamic Economics, which positions the Qur'an and As-Sunnah as the legal basis, of course there are signs of halal and haram. There are several forms of transactions in society that are already common among them are ribawi transactions (interest), maisir (gambling), tadlis (fraud), ihtikar (hoarding), ghisysy (covering defects), ghabn (price fraud) and gharar (speculation), aspects of justice, efficiency, welfare. Whereas in Islamic consumption everyone should look at and try to prioritize maslahah compared to utility.